2020
DOI: 10.1016/j.bpj.2020.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Insulin Amyloid Polymorphism Using Raman Spectroscopy and Imaging

Abstract: Our results revealed three Raman markers distinguishing amyloid fibril polymorphisms caused by salt and temperature effects; the relative proportion of protein secondary structures (α-helix and β-sheet), the ratio of tyrosine doublet, and the conformational differences of disulfide bonds.The lower values of tyrosine doublet in the case with salts were interpreted as the anions rob the hydration water from proteins which induced protein misfolding. Using these parameters, Raman images captured their higher orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…More generally, the monomeric structures of several disease-related amyloidogenic proteins other than α-synuclein are also known to be affected by NaCl concentration, which in turn leads to altered aggregation pathways. Those proteins include Aβ(1–40), , IAPP, β 2 -microglobulin, , insulin, or the antimicrobial peptide uperin 3.5 . The suggested underlying mechanisms seem to be highly diverse, ranging from the aforementioned Debye–Hückel screening, specific ion–protein interactions and solvent-structure changes to the induction of specific secondary structure elements.…”
Section: Resultsmentioning
confidence: 99%
“…More generally, the monomeric structures of several disease-related amyloidogenic proteins other than α-synuclein are also known to be affected by NaCl concentration, which in turn leads to altered aggregation pathways. Those proteins include Aβ(1–40), , IAPP, β 2 -microglobulin, , insulin, or the antimicrobial peptide uperin 3.5 . The suggested underlying mechanisms seem to be highly diverse, ranging from the aforementioned Debye–Hückel screening, specific ion–protein interactions and solvent-structure changes to the induction of specific secondary structure elements.…”
Section: Resultsmentioning
confidence: 99%
“…60 It has been established that unique tau conformers exist in different tauopathies, [4][5][6][7][8]13,61 and that conformers from disease differ to those formed in vitro, 62,63 possibly due to differences in the available cofactor, 13 PTM, 19 local pH or ion environment. 23,25 Emerging evidence suggests that different populations of soluble tau aggregates may exist between different AD patients and that the presence of a given population may correlate with disease onset and progression. 20 We have shown that changes in the physiochemical environment can lead to the formation of distinct tau conformers, reinforcing the possibility that different conformers may also occur in different disease settings.…”
Section: The Utility Of Raman Spectroscopy For Characterizing and Dismentioning
confidence: 99%
“… 24 Recently Raman spectroscopy was used to identify conformational polymorphism of insulin amyloid fibrils in different buffer conditions. 25 It is yet to be determined whether fibril polymorphism, aggregation cofactor, PTM or primary sequence have an impact on the Raman spectrum of tau aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…33 Moreover, in situ Raman imaging of amyloid aggregates by M. Ishigaki et al confirmed the presence of various polymorphs within insulin spherulite-like structures, based on the analysis of the relative proportion of β-sheet structures, the intensity ratio of the tyrosine doublet and the signal intensity arising from the disulfide bonds. 34 A drastic drop of the ThT fluorescence intensity near the core suggests that even though mature fibrils may be present there, the dye is not capable of properly staining them. We hypothesize that the aforementioned limitation may arise from the lack of accessibility of ThT molecules to fibrils formed de novo inside the core, or due to distortion of the binding sites of polymorphs formed in the initial state of superstructure growth.…”
Section: Resultsmentioning
confidence: 99%